Pengaruh Kadar Air dalam Minyak Kemiri Sunan pada Tahap Esterifikasi dengan Katalis Asam Sulfat (Jurnal Ilmiah Teknologi Pertanian Agrotechno, 2023)
Kemiri sunan oil is non-food oil. Therefore, kemiri sunan oil can be a potential raw material for biodiesel synthesis. Kemiri sunan oil has relatively high free fatty acid content so that before the transesterification step with a homogeneous base catalyst it is necessary to esterify it first. In esterification, the water content in oil and fat as raw material for biodiesel affects the conversion rate of free fatty acids into biodiesel, so this needs to be studied. The purpose of this study was to study the effect of water content in kemiri sunan oil on the conversion of free fatty acids into biodiesel at the esterification stage. The research was conducted by quantitative experiment. Variations of water content in kemiri sunan oil were obtained through evaporation at a temperature of 105 oC with time variations of 1, 1.5 and 2 hours. Esterification was carried out at a temperature of 60 oC, mole ratio of oil to methanol of 1:6, reaction time of 1.5 hours, and 98% sulfuric acid catalyst as much as 1%. The results showed that the less water content in the kemiri sunan oil, the less free fatty acids contained in the biodiesel from the esterification result.
Keywords: biodiesel; esterifikasi; minyak kemiri sunan; kadar air